When police discursive violence interacts with intimate partner violence: Domestic Violence as a risk factor for police-induced false confessions - Ainsworth, Janet (Language and Law / Linguagem e Direito, 2022)
Linguists analyzing the practices of American-style police interrogation have revealed the discursive attributes of police interrogation that can, often unwittingly, induce false confessions from suspects. Further, psychologists have identified a number of factors that can make particular subjects of police interrogation especially vulnerable to false confessions under interrogation. This article suggests that women who have been victims of serial domestic violence may be a heretofore unrecognized class of those particularly vulnerable individuals. Because the psychodynamics of American-style police interrogation so closely parallel the psychodynamics of intimate terroristic domestic violence, victims of domestic violence may react to police interrogation with the same coping strategies – accommodation and acquiescence – that they resort to in attempting to avoid battering. In the context of police interrogation, that would potentially lead to false confessions. Collaborative research by linguists and psychologists is needed to mitigate this possibility for miscarriages of justice.